Comprehensive knowledge of HIV prevention among fishing communities of Lake Kyoga, Uganda, 2013 - Leocadia Kwagonza; Lilian Bulage; Paul Edward Okello; Joy Kusiima; Daniel Kadobera; Alex Riolexus Ario (BMC, 2020)
Abstract Background Compared to the general population in Uganda, fishing communities suffer greater burden of HIV/AIDS. We determined the level of comprehensive knowledge on HIV prevention and its associated factors among fishing communities of Lake Kyoga. Methods We conducted secondary analysis of data from the Lake Kyoga Behavioral Survey, a population-based sample survey on behavioral risk factors for HIV, syphilis, and schistosomiasis among adults in fishing communities of Lake Kyoga in 2013. We defined comprehensive knowledge as having correct knowledge on HIV prevention (consistent condom use, faithfulness, a healthy-looking person can have HIV, and HIV cannot be transmitted through food-sharing, witchcraft or handshake). We used logistic regression to determined potential factors associated with comprehensive knowledge on HIV prevention and control for confounding. Results Of 1780 persons in the sample, 51% (911/1780) were females. The mean age was 32 (range: 15-97) years. Overall, 51% (899/1780) of persons had comprehensive knowledge on HIV prevention. Level of comprehensive knowledge on HIV prevention was similar between females (52%, 449/911) and males (49%, 450/869). Males (76%, 658/869) had lower knowledge on HIV transmission from mother to child during breast feeding compared to females (81%, 738/911) (p-value 0.019). Fishermen (46%,324/711) who lived > 5 km away from a health center compared to 54% (572/1066) who lived within 5 km radius were less likely to have comprehensive knowledge on HIV prevention (PRRadj = 0.8; 95%CI = 0.5-0.92). Those who had ever tested for HIV were more likely to have comprehensive knowledge of HIV transmission (PRRadj = 1.1; 95% 1.03-1.70). Conclusion Half of the population of Lake Kyoga fishing community had comprehensive knowledge of HIV prevention. Long distances from health facilities reduced the level of comprehensive knowledge on HIV transmission. HIV testing increased the level of comprehensive knowledge on HIV transmission. Ministry of health should ensure that HIV/AIDS information; education and communication and HIV counseling and testing activities are intensified in fishing communities of Lake Kyoga, with more emphasis on communities living in distances of more than 5 km away from the health facility.